The Effect of Motivation and Work Discipline on Performance of Locket Officers at PT KCI Rute Jakarta Kota Bogor - Abul Latif Muqaffi; Wahyuddin Latunreng; Rudi Hermawan; Antoni Ludfi Arifin (Budapest International Research and Critics University, 2022)
The object of this study is to find out the correlation between motivation and work discipline on the performance of counter officers. The objective is to find out how much motivation and work discipline can boost the performance of counter officers at the Jakarta Kota-Bogor Commuter Line Stations. The data for this research was collected with the Questionnaire and Literature Study methods. The method used for this study is the quantitative analysis method. The sample population for this study was 137 PT KCI counter officers working at the Jakarta Kota-Bogor Commuter Lina Stations. The results of the study are: a) The results of the correlation coefficient of (r) X1 against Y is 0.459 or 45.9%, which based on the correlation interpretation table means that there is a moderately high correlation between the motivation variable and officer’s performance variable. The higher the value of the correlation cofficient means the greater the effect and correlation berween the X1 variable and the Y variable. The amount of correlation on how the X1 variable affects the Y variable is around 45.9%; b) the results of the correlation coefficient (r) X2 against Y is 0.722 or 72. 2%, which based on the correlation interpretation table shows that there is a strong or high correlation between the discipline variable and the officer performance variable. The greater the correlation coefficient value means the stronger the correlation is between the X2 variable and Y variable. The amount of how the X2 variable will affect the Y variable is 72.2%; and c) the results of the correlation coefficient (r) of X1 and X2 to Y show the value of the correlation coefficient (r) between the variables of motivation (X1) and discipline (X2) together with officer performance (Y) of 0.732. This value reflects that the relationship between motivation (X1) and discipline (X2) together with officer performance (Y) qualitatively is a very strong and positive correlation of 73.2%. Based on the interpretation table, the multiple correlation coefficient (r) is an estimate of how far the correlation between the two or more independent variables is from the dependent variable. The correlation coefficient between variables is aroun 0-1. If the result of r is closer to one (1), the the influence of the independent variable on the dependent variable is bigger. If the result of r is closer to zero (0), then the influence of the independent variable is weaker on the dependent variable.